2020
DOI: 10.1186/s12886-020-01372-6
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal vein occlusion secondary to severe iron-deficiency anaemia resulting from a plant-based diet and menorrhagia: a case presentation

Abstract: In this case presentation, we present a young vegan patient who developed a CRVO secondary to severe irondeficiency anaemia (IDA) attributable to menstrual losses and limited iron intake. CRVO is a rare complication of IDA. With rising calls for sustainable diets and rising evidence for a plant-based diet, there has been a rise in popularity of such diet forms. While there are ocular benefits from this diet trend, the potential for nutritional deficiencies including iron needs to be monitored especially in sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…CRVO and amenorrhea contributed by IDA were reported in the literature before but this was the first case that was precipitated by COVID-19 related movement restrictions. 3 4 Disruption to diet and hence health is common when countries institute COVID-19 lockdown measures. 10 There are literatures that revealed that lockdown resulted in people purchasing more chips/snacks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CRVO and amenorrhea contributed by IDA were reported in the literature before but this was the first case that was precipitated by COVID-19 related movement restrictions. 3 4 Disruption to diet and hence health is common when countries institute COVID-19 lockdown measures. 10 There are literatures that revealed that lockdown resulted in people purchasing more chips/snacks.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Many mechanisms were hypothesised to explain thrombosis in IDA including endothelial injury, reactive thrombosis and hypercoagulability. 3 5 6 Factors including diet and lifestyle have also been investigated. 20 Iron is important for metabolism and phototransduction of the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulated coagulation from iron deficiency anaemia can contribute to central retinal vein occlusion and cilioretinal artery occlusion; when present, reactive thrombocytosis and hypoxia induced endothelial injury can also contribute 123…”
mentioning
confidence: 99%